Pengaruh Kepemimpinan Transformasional Dan Pelatihan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pengadilan Negeri Pariaman - Husna, Fidya Tul; Sari, Marta Widian; Pondrinal, Muhammad (CV. ITTC INDONESIA, 2026)
This study aims to determine the effect of transformational leadership and job training on employee performance with job satisfaction as an intervening variable at the Pariaman District Court (Pengadilan Negeri Pariaman). The research method used was quantitative with a total sampling technique, involving the entire population of 33 employees as respondents. Data collection was conducted through questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach utilizing SmartPLS 3.0 software. The results showed that transformational leadership and job training had a significant effect on job satisfaction. Directly, transformational leadership, job training, and job satisfaction also had a significant effect on employee performance. Path analysis findings proved that job satisfaction is able to mediate the effect of transformational leadership on employee performance. However, job satisfaction was found unable to mediate the effect of job training on employee performance. The contribution of independent variables to employee performance was recorded at 87.2%..